A Design-Science-Based Technical-Security Framework for IoMT: Empirical Validation in Resource-Constrained Hospitals - Arinaitwe Winfred; Kareyo Margaret; Shefiu Olusegun Ganiyu (Institut Teknologi Dirgantara Adisutjipto, 2026)
The rapid diffusion of Internet of Medical Things (IoMT) technologies has improved healthcare delivery through real-time monitoring and data exchange, yet secure information sharing remains challenging in resource-constrained healthcare environments. This study develops and empirically validates a technical-security systems engineering framework integrating device, network, application, and governance layers for information-sharing-enabled IoMT systems in low-resource hospitals. The study adopted a Design Science Research (DSR) approach involving two phases: (1) qualitative derivation of security requirements from literature and standards, and (2) quantitative empirical validation using multiple regression analysis based on hospital survey data (n = 148). The study contributes a technical-security systems engineering framework that integrates device security, network protection, interoperability mechanisms, governance structures, and contextual adaptation requirements into a unified architectural model. Empirical findings indicate that secure IoMT implementation depends on the coordinated interaction of technical, organizational, and contextual controls rather than isolated cybersecurity mechanisms. By translating socio-technical interdependencies into operational security requirements aligned with standards promoted by the National Institute of Standards and Technology, the study provides a validated design-science artifact that supports secure IoMT deployment in emerging digital health ecosystems, particularly within resource-constrained healthcare systems.